Reports from Parents about Medical and Low Vision Services for Their Children with Albinism: An Analysis. (November 2018) - Corn, Anne L.; Lusk, Kelly E.
Introduction: The purpose of this study was to gain information from parents in the United States about their children with albinism. The article focuses on information and services related to medical care and low vision care. Methods: An online questionnaire was used to collect data, and parents had opportunities to submit additional information. One hundred ninety-two families, representing 223 children with albinism from 40 U.S. states, completed surveys. Results: A snapshot of the data indicates that for 8.6 out of 10 families, there were no known relatives with the condition; 55.8% of the children had visual acuities that met the criteria for legal blindness in the United States; and 48% of the children using optical devices had received clinical low vision evaluations by optometrists or ophthalmologists who specialized in low vision. Implications for practitioners: The data gathered suggest recommendations for medical service providers, including clinical low vision specialists who perform evaluations for improving the functional use of vision.